Nghiên cứu thí điểm sách giáo khoa điện tử dễ tiếp cận định dạng EPUB cho học sinh khuyết tật nhìn - Nguyễn Thị Hằng, Nguyễn Thị Hằng; Trần Thị Văng, Trần Thị Văng; Nguyễn Minh Châu, Nguyễn Minh Châu; Đào Thu Hương, Đào Thu Hương (Tạp chí Giáo dục, 2026)
This pilot study evaluates the impact of accessible EPUB textbooks on students with visual impairments in grades 7 and 9 in Hanoi and Da Nang. Conducted from December 2024 and June 2025, it involved 42 students, 17 teachers, and 15 parents, and employed qualitative methods including surveys, in-depth interviews, and classroom observations. Findings reveal a serious shortage of learning materials: Braille textbooks remain bulky, limited in subjects coverage and forces students to rely heavily on teachers. The introduction of EPUB textbooks improved access, autonomy, and study habits, receiving positive feedback from both parents and teachers. The pilot also provides initial evidence on the effectiveness of the model for nationwide conversion and free distribution of accessible e-textbooks, showing its potential to reduce learning inequities for students with visual impairments. Despite existing technical barriers, the study confirms the feasibility and scalability of EPUB textbooks as an effective solution for inclusive education in the digital. The model is one of the products of the collaboration between the United Nations Development Programme (UNDP) and the Vietnam National Institute of Educational Sciences (VNIES).